THE CONDITIONS OF SUCCESS OF CHINESE INVESTMENT MODEL - X. Han (Вестник университета)
The practice of investing in Russian projects by Chinese entrepreneurs is considered. The main key areas of investment, gives examples and statistics on this issue are identified. The information on direct and portfolio investments, on the investment activity of the Russian Federation, on Chinese investments of private investors and the results of investment agreements at the government level is provided. The article deals with the formation of the Russian-Chinese investment Fund, the work of the Russian-Chinese intergovernmental Commission.